2019
DOI: 10.20473/bhsj.v2i2.14900
|View full text |Cite
|
Sign up to set email alerts
|

‘Wanting’ and ‘Liking’ Brain Mechanisms in Coaching: A qEEG Study using the CARE Coaching Model

Abstract: Introduction: Coaching has become increasingly popular for leadership development and behavioral change in organizations. Recent studies suggest that motivation is essential in enhancing the effectiveness of workplace coaching. A number of studies revealed that delta and beta-gamma oscillations are associated with the human motivational process through ‘wanting’ and ‘liking’ mechanisms. However, the brain mechanisms of motivation in coaching have not been studied. This preliminary study is the first attempt to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Puspa and colleagues [134] found that when a coach helps a coachee set new personal goals and a plan to achieve them, on the one hand, there is an increase in delta activity in the left prefrontal, frontal, central parietal, and occipital regions, and on the other hand, there is an increase in beta-gamma activity in the frontal, posterior temporal, and occipital areas. The delta and beta-gamma bands have been linked to the two motivational mechanisms of wanting and liking, respectively [135,136].…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 99%
See 1 more Smart Citation
“…Puspa and colleagues [134] found that when a coach helps a coachee set new personal goals and a plan to achieve them, on the one hand, there is an increase in delta activity in the left prefrontal, frontal, central parietal, and occipital regions, and on the other hand, there is an increase in beta-gamma activity in the frontal, posterior temporal, and occipital areas. The delta and beta-gamma bands have been linked to the two motivational mechanisms of wanting and liking, respectively [135,136].…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 99%
“…Wanting refers to the motivation to achieve a rewarding result. Liking indicates the imagined anticipation of the hedonic state of pleasure resulting from achieving the goal [134,[137][138][139].…”
Section: Neurocoaching: a Neuroscientific Approach To Coachingmentioning
confidence: 99%